Histamine release from tissues during transfusion shock from transfusion of incompatible blood (Revista Española de Fisiología, 1948)
1. The shock condition which the transfusion of heterologous blood produces in the dog, would be due to histamine liberation from the tissues, as is shown by the fact that the antihistaminic substances like benadryl, produce a marked decrease of the intensity of the vascular and respiratory symptoms.2. The outstanding role played by the liver in the production of shock by transfusion is evidenced by the decreased reactivity of the animals after the exclusion of this organ by ligature of the liver artery and an Eck’s fistula (anastomosis between vena porta and vena cava).3. The rabbit that reacts to histamine injections by increase of arterial presure, shows similar reactions following the injection of heterologous blood.4. The injection of relatively largs quantities of incompatible blood produces a long lasting shock, which may lead to death or to the animal’s recovery, and which coincides with hemoconcentration, increase of total acid soluble plasma phosphorus, and also with little meaning variations of blood potassium.